Amendments and additions to the twenty-second edition of the dictionary of the Royal Academy of the Spanish Language: the Peruvian proposal - Portilla Durand, Luisa P. (2002)
In October of this year (2001), the twenty-second edition of the Dictionary of the Royal Academy of the Spanish Language was published. document in which a group of Peruvian professionals was involved.